Estimating sulfide capacities for ternary systems with limited solubility - Wang L.J.; Liu Q.Y.; Chou K.C. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In view of successful application of mass triangle model in thermophysical properties, in the current work, the mass triangle model was extended to evaluate sulfide capacities of ternary systems with limited homogeneous region. Four ternary systems of Al2O3-FeO-SiO2, FeO-CaO-SiO2, CaO-CaCl2-CaF2 and CaO-CaF2-SiO2 were chosen to calculate iso-sulfide capacity based on the limited boundary data. The good agreement between reference data and calculated data indicated that this model is feasible and will play an indispensable role in the future. Compared with optical basicity model, the results obtained by mass triangle model are still competitive when containing Cl- and F- in the molten slag due to lacking the optical basicity values.